Communications Server for z/OS V1R8 TCP/IP implementation. - White, Bill (Telecommunications engineer); Miyamoto, Yukihiko; Oliveira, Gilson Cesar de; Peschke, Roland (IBM redbooks., 2007)
In this IBM Redbooks publication we begin with a discussion of Virtual IP Addressing (VIPA), a TCP/IP high-availability approach introduced by the z/OS Communications Server. We then proceed to show how VIPA can be used for high availability—both with and without using a dynamic routing protocol. Then we discuss a number of different workload balancing approaches that can be used with the z/OS Communications Server. In this book we use the terms internal and external application workload balancing to refer to approaches where the decision as to which application instance should received a given connection request is made within the sysplex environment (such as by Sysplex Distributor) or outside of it (using a separate, external, workload balancing solution), respectively. Finally, we explain the optimized Sysplex Distributor intra-sysplex load balancing. This function is an improved multi-tier application support using optimized local connections together with weight values from extended WLM interfaces.